É possível propor a formação de leitores nas disciplinas de Ciências Naturais? Contribuições da análise de discurso para a educação em ciências. - Suzani Cassiani; Patrícia Montanari Giraldi; Irlan von Linsingen (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
Understanding reading as a place of production of meaning, we problematize the understandings of writing, reader, author, pointing out some contributions/ implications for science education. When we focus on the formation of readers, we work with the stories of students reading as part of the production conditions of reading in class. This contributes significantly to deepen the understanding of relations between texts and readers. By the same token, it emerges the relationship of students with writing, exploited by us in view of authorship, understood as social position assumed by the subject that in interpreting (write/read) affiliated to a network of meanings. It is from this relationship established between subjects, with their stories, and different social meanings that circulate within and outside the school, which are produced meanings about science and technology. Finally, in problematizing the very language of / in science education, our intend is to contribute to the promotion of a education committed to questioning the sciences and their social roles.